Complete regression of primary cutaneous malignant melanoma associated with distant lymph node metastasis: a teaching case mimicking blue nevus. (December 2016) - Yamada, Sohsuke; Nawata, Aya; Yoshioka, Manabu; Hiraki, Tsubasa; Higashi, Michiyo; Hatanaka, Kazuhito; Tanimoto, Akihide
Abstract Background Malignant melanoma (MM) tends to be spontaneously regressed, however, complete regression of primary cutaneous MM is an extremely rare phenomenon. Our aim is to be aware that pathologists and/or dermatologists can readily misinterpret it as the other benign or malignant lesions. Case presentation A gradually growing and verrucous hypopigmented macule had been noticed in the right sole of a 65-year-old Japanese male since 2 years before, and it turned to be a solitary bluish to black patch with surrounding depigmentation and was recently decreased in size. In parallel, the patient had a rapidly growing black-pigmented mass lesion at the right inguen. The cutaneous specimen from the sole showed an aggregation of many melanophages predominantly in the middle to deep layer of dermis, associated with surrounding fibrosis, reactive vascular proliferation and CD8-positive T-lymphocytic infiltrate, covered by attenuated epidermis with absence of rete ridge. However, no remnant MM cells were completely seen in the step-serial sections. We first interpreted it as blue nevus. By contrast, the inguinal mass revealed a diffuse proliferation of highly atypical mono- to multi-nucleated large cells having abundant eosinophilic cytoplasm in the enlarged lymph node tissue. Immunohistochemical findings demonstrated that these atypical cells were specifically positive for HMB45 and Melan A. Therefore, we finally made a diagnosis of complete regression of primary cutaneous MM associated with distant lymph node metastasis of MM. Conclusion Careful, not only general/cutaneous but histopathological, examinations should be necessary and adjunctive aids for reaching the correct diagnosis of complete regression of cutaneous MM.